2011
DOI: 10.1007/s10734-011-9407-1
|View full text |Cite
|
Sign up to set email alerts
|

A positive postdoctoral experience is related to quality supervision and career mentoring, collaborations, networking and a nurturing research environment

Abstract: For postdocs to have the best chances of achieving their career goals they need to not only acquire discipline-specific research experience, but also additional generic skills vital for future employment inside or outside academia. They also require access to information and mentoring that will help them strategically plan and make informed decisions about their future. Few studies have examined the variables that impact the postdoctoral experience or research productivity. Thus, a comprehensive survey was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 6 publications
4
102
0
Order By: Relevance
“…Studies focusing on academic careers are increasingly available, but only a few (see Table 1 for an overview) deal explicitly with the career prospects of postdocs (e.g., Bessudnov et al 2014;Davis 2009;De Goede et al 2013;Felisberti and Sear 2014;Fitzenberger and Schulze 2013;Mitchell et al 2013;NISTEP 2008NISTEP , 2009Scaffidi and Berman 2011;Stanford et al 2009). The Australian study by Scaffidi and Berman (2011) examined the variables that impact the postdoctoral experience or research productivity to determine whether quality of supervision, career mentoring, collaboration, networking, and a nurturing research environment made positive differences in the experiences and productivity of postdoctoral researchers. They confirmed that job insecurity and a lack of career structure continue to be ongoing concerns for postdocs, but they also revealed a clear link between the quality of supervision and a positive postdoc experience, particularly when supervisors take responsibility for their postdocs' future career prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on academic careers are increasingly available, but only a few (see Table 1 for an overview) deal explicitly with the career prospects of postdocs (e.g., Bessudnov et al 2014;Davis 2009;De Goede et al 2013;Felisberti and Sear 2014;Fitzenberger and Schulze 2013;Mitchell et al 2013;NISTEP 2008NISTEP , 2009Scaffidi and Berman 2011;Stanford et al 2009). The Australian study by Scaffidi and Berman (2011) examined the variables that impact the postdoctoral experience or research productivity to determine whether quality of supervision, career mentoring, collaboration, networking, and a nurturing research environment made positive differences in the experiences and productivity of postdoctoral researchers. They confirmed that job insecurity and a lack of career structure continue to be ongoing concerns for postdocs, but they also revealed a clear link between the quality of supervision and a positive postdoc experience, particularly when supervisors take responsibility for their postdocs' future career prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was not possible to identify the supervisors of the respondents. As a consequence, this study draws an incomplete picture of the antecedents of academic career insecurity, since the number of job vacancies, individual performance, and the supervisor's capabilities and reputation affect career opportunities (Scaffidi and Berman 2011;van der Weijden et al 2016). Thus, future research taking these factors into account is needed.…”
Section: Discussionmentioning
confidence: 99%
“…McEvily, Jaffee, and Tortoriello 2012), which then affect academics long-term career paths as well. Third, the access to the mentors' networks proves important for the career development of mentees, because mentees become visible in the mentors' network of colleagues and gain access to their social capital (Johnson 2007;Scaffidi and Berman 2011;Lutter and Schröder 2016).…”
Section: Mentor-mentee Heterogeneity: the Role Of Phd Supervisorsmentioning
confidence: 99%